Effect Of Work Stress On Mental Well-Being With Workplace Spirituality As A Mediating Variable - Rizaldi, Hamza (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to evaluate the effect of work stress on the mental well-being of medical personnel and to examine the mediating role of workplace spirituality at Arosuka Regional General Hospital, Solok Regency. Methodology: The research employs a quantitative survey approach. The study population consists of 162 medical personnel, with 116 respondents selected using simple random sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares (SmartPLS). Results: The results indicate that work stress has a significant negative effect on the mental well-being of medical personnel. Additionally, workplace spirituality is proven to mediate the relationship between work stress and mental well-being by reducing the negative impact of stress. Novelty: This study highlights workplace spirituality as an important psychological resource in managing occupational stress within healthcare institutions. Findings: Strengthening workplace spirituality can help medical personnel cope more effectively with work stress and improve their mental well-being. Originality: The originality of this study lies in its empirical examination of workplace spirituality as a mediating variable in a hospital setting, which remains limited in previous research. Conclusions: Integrating workplace spirituality into stress management strategies is essential to maintaining and enhancing the mental well-being of medical personnel. Type of Paper: Empirical Quantitative Research Paper